Engineered dendritic cells for gastrointestinal tumor immunotherapy: opportunities in translational research. (February 2013) - Bhargava, Arpit; Mishra, Dinesh; Banerjee, Smita; Mishra, Pradyumna Kumar
<x xml:space="preserve">Abstract</x> Gastrointestinal (GI) malignancies are one of the most frequently occurring tumors found worldwide. Surgery remains the primary treatment for most solid tumors and adjuvant chemotherapy and radiotherapy are limited by lack of specificity and toxicity. In view of the poor survival rate, there is a great need to introduce new and effective therapeutic modalities. Recently, dendritic cells (DCs)-based vaccines are being explored as a promising therapeutic strategy but their success is limited by the tumor-induced immune escape mechanisms. This article provides a comprehensive analysis of clinical trials conducted using this approach. It also showcases the necessity of exploring nano-engineered strategies for improving the clinical utility of DC-vaccination for GI tract malignancies to overcome immune tolerance.